The Role of Prohepcidin in Anemia Due to Helicobacter pylori Infection. (1st August 2013) - Ozkasap, Serdar; Yarali, Nese; Isik, Pamir; Bay, Ali; Kara, Abdurrahman; Tunc, Bahattin
Abstract : Background: Hepcidin, a key regulator of iron homeostasis, increases when inflammation and some infections occur. It plays a critical role in macrophage iron retention, which underlies inflammation/infection caused anemia. It is known that Helicobacter pylori (HP) may lead to iron deficiency (ID) due to occult blood loss or reduced iron absorption. This study investigates the role of prohepcidin, hepcidin's precursor, in ID and ID anemia (IDA) with a concurrent HP infection. Methods: In this prospectively designed study, 15 patients with IDA and a concurrent HP infection (group 1), 11 patients with an ID and a concurrent HP infection (group 2), and 18 patients with HP infection (group 3) were observed. All groups received only HP eradication therapy. Twenty-five age- and sex-matched children without ID/IDA and HP infection were included in the study as the control group. In all groups and control group, measurements were taken for pre- and posttreatment hemoglobin, serum prohepcidin, serum ferritin, serum iron (SI), transferrin saturation, erythrocyte sedimentation rate, fibrinogen, and C-reactive protein levels. Results: The pretreatment prohepcidin levels were significantly higher only in group 1 compared to the control group ( P < .05). In group 1, a significant increase in hemoglobin and SI levels and a significant reduction in prohepcidin levels were additionally observed following HP eradication treatment ( P < .05). However, in groups 2 and 3, significant differences in hemoglobin, iron, and prohepcidin levels between pre- and posttreatment were not observed. Conclusion: Elevated serum prohepcidin might indicate the role of inflammation in the etiology of anemia concurrent with HP.